Effectiveness of the Inter-american Human Rights System in the context of the protection of indigenous collective rights - Pihuave Mendoza, Pedro Pablo (2025)
The main purpose of this study was to evaluate the effectiveness of the Inter-American Human Rights System in defending and protecting the collective rights of Indigenous communities, focusing on the treatment of legal pluralism, multiculturalism, and universal human rights as the foundation for this reflection. The study adopted a qualitative and doctrinal approach, examining theories and specialized research on the relationship between cultural relativism and universal human rights. The findings highlight that, although the Inter-American Human Rights System has achieved notable progress in the normative validation of collective rights, a tension persists between cultural relativism and universal rights. Additionally, the lack of political will and institutional fragility limit the impact of the international court’s rulings. However, these rulings have set precedents that strengthen legal pluralism as an instrument of emancipation. This study underscores the importance of continuous intercultural dialogue and a strong political commitment to ensuring inclusive justice that respects both the cultural autonomy of Indigenous communities and the fundamental principles of human rights.